Implementasi Algoritme Shazam untuk Mengidentifikasi Hadis dan Surah dalam Al-Quran Menggunakan Suara - Bahruddin El Hayat; Imam Cholissodin; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
For muslims, understanding Al-Qur'an and Hadis are an obligation because those two is the basic of Islam. In the learning process, a person usually will begin by memorizing the pronounciation and the surah's or hadis's name. After the person can pronounce the surah or hadis fluently, then they will continue to understand the meaning and the content of the surah or hadis. The problem is sometimes a person can forget the name of surah or hadis when another person says a verse from the surah or hadis. So, a solution is needed to handle the problem. In this research, the writer offers a solution to build a system that can identify the name of surah or hadis in Al-Qur'an by taking an input in the form of a sound file with WAV extension using Shazam algorithm. The identification process is done by doing these following actions: numeric value extraction, conversion, feature extraction, filtering and matching. The result is the name and information of the surah or hadis. The best accuracy from identifying surah and hadis from Al-Qur'an is 82% in the testing phase using a test data with 15 second duration, chunk size=4096 and range=60.